Effect of Fibre Content on Compressive Strength of Reinforced Soil - Chegenizadeh, Amin; Nikraz, Hamid (Australian Geomechanics Society, 2011)
This paper aims to investigate effect of using fibre on strength of composite. A series of laboratory tests has been carried out to investigate the using of plastic fibre as reinforcement to increase the strength of the soil composite. Fibre percentage varied from 0% (for unreinforced samples) to 0.3%. Two methods of compaction test were used (i.e. Standard and Modified compaction methods). Unconfined compression tests were conducted in this study. The objective of using unconfined compression test was to determine the UU (unconsolidated, undrained) strength of a cohesive soil in an inexpensive manner. The results showed that fibre dosage was significant factor that affected the strength of the soil specimens. The results also indicated increasing in fibre content caused increase in compressive strength. The strength and ductility considerably increased with increasing the fibre content. Furthermore, Unconfined Compression Strength (UCS) found to be slightly greater for Modified method than Standard one. In addition, a series of tests have been conducted to examine permeability coefficient of the specimens. The results showed that length and fibre dosage had considerable effects on permeability of samples. It was proved that increase in fibre content and length caused increase in hydraulic conductivity.